Public Management Innovation and Public Service Reform in the ASEAN Economic Community Era - Susi Sugiyarsih (International Journal of Science Education and Cultural Studies, 2023)
The implementation of the AEC has increased competition among member countries and has required governments to enhance their capacity to deliver efficient, responsive and competitive public services. Innovation in public management has been an important strategy to improve national competitiveness and to support sustainable economic development. The paper discusses the role of public management innovation and public service reform in improving Indonesia’s readiness and competitiveness in the era of the ASEAN Economic Community. This research uses a narrative literature review method to review some concepts of public management innovation, public service reform, human resource development, and the implementation of PTSP as a strategy to improve service effectiveness and efficiency. The discussion suggests that public service innovation is important for streamlining administrative procedures, improving service quality and creating a more conducive environment for economic activity and investment. Furthermore, effective public service reform necessitates the existence of competent human resources, institutional commitment and sustained efforts to improve the governance practices. Thus, improving Indonesia’s competitiveness in an increasingly integrated regional economy is still crucial in terms of boosting public management innovation and public service reform.